2019
DOI: 10.1016/j.ygcen.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone disruption on the ontogenetic expression of thyroid hormone signaling genes in developing zebrafish (Danio rerio)

Abstract: Thyroid hormones (THs) regulate neurodevelopment, thus TH disruption is widely posited as a mechanism of developmental neurotoxicity for diverse environmental chemicals. Zebrafish have been proposed as an alternative model for studying the role of TH in developmental neurotoxicity. To realize this goal, it is critical to characterize the normal ontogenetic expression profile of TH signaling molecules in the developing zebrafish and determine the sensitivity of these molecules to perturbations in TH levels. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 75 publications
8
41
0
Order By: Relevance
“…Therefore, the increased levels of dio1 and dio2 transcripts observed here provide strong evidence of an induced systemic hypothyroid condition in the TBBPA and BDE-47 exposed zebrafish larvae [76][77][78]. This likelihood is supported by the reduced dio3b mRNA levels observed in whole larval (96 hpf) samples exposed to TBBPA (0.18 and 0.46 µM groups), since D3 is the major inactivating pathway of THs and thyroidal status often parallels hepatic D3 activity, increasing during hyperthyroidism and decreasing during hypothyroidism [33,79].…”
Section: Effects Of Tbbpa and Bde-47 On Deiodinase Expressionsupporting
confidence: 68%
“…Therefore, the increased levels of dio1 and dio2 transcripts observed here provide strong evidence of an induced systemic hypothyroid condition in the TBBPA and BDE-47 exposed zebrafish larvae [76][77][78]. This likelihood is supported by the reduced dio3b mRNA levels observed in whole larval (96 hpf) samples exposed to TBBPA (0.18 and 0.46 µM groups), since D3 is the major inactivating pathway of THs and thyroidal status often parallels hepatic D3 activity, increasing during hyperthyroidism and decreasing during hypothyroidism [33,79].…”
Section: Effects Of Tbbpa and Bde-47 On Deiodinase Expressionsupporting
confidence: 68%
“…Tight regulation of circulating hormones by the HPT axis is well conserved across vertebrates, and the structure and function of key components TH signalling in teleosts closely resemble those of higher vertebrates. Using zebrafish exposed to exogenous THs or PTU (with or without an mct8 morpholino) at 24, 72 and 120 h post-fertilization (hpf), Walter et al (2019) confirmed that expression of key ortholog genes which mediate TH signalling in mammals appear to be coordinated by THs in D. Rerio. However, in teleosts, thyroid follicles (the functional unit of the gland) are dispersed along the ventral midline of the pharynx instead of being encapsulated in an organized pair of thyroid glands (Alt et al, 2006), which therefore precludes the use of histopathological assessment as is employed in Xenopus and mammals.…”
Section: Teleost Fish Models For Identification Of Thyroid Disruptionmentioning
confidence: 76%
“…Remarkably, specific biomarkers for thyroid disruption in teleost fishes have yet to be accepted for regulatory purposes due to discrepancies resulting from inconsistent experimental parameters across a limited amount of studies using known TH disruptors, as emphasised by Spaan et al (2019). However, given the relatively recent characterization of the zebrafish HPT axis and intrinsic advantages, the zebrafish is becoming a promising alternative vertebrate model for thyroid signalling, amenable to highthroughput screening owing to their small size, ease of culture and short generation time (Haggard et al, 2018;Kollitz et al, 2018;Marelli and Persani, 2017;Noyes et al, 2018;Sipes et al, 2011;Vancamp et al, 2018;Walter et al, 2019).…”
Section: Teleost Fish Models For Identification Of Thyroid Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the expression of TH signaling molecules at later stages of neurodevelopment, including axonal and dendritic outgrowth, and synaptogenesis, we performed transcriptomic analyses of rat primary neuron-glia co-cultures derived from PND 1 rat cortex that were cultured for up to 21 days in vitro (DIV) [23]. Finally, we also examined the ontogenetic profile of these transcripts in zebrafish larvae since this model has been proposed as an alternative organism for screening the DNT potential of TH active chemical compounds [24,25]. Moreover, zebrafish offer the potential for future studies to integrate molecular effects of TH disruption with physiological and behavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%